The Influence of Complex Distractors in the Remote Distractor Paradigm - Valerie Benson (Bern Open Publishing, 2008)
Three experiments examined the influence of complex dis-tractors on the Remote Distractor Effect (RDE), a robust finding of an increase is saccade latencies when two, rather than one possible targets are presented simultaneously (Walker, Deubel, Schneider & Findlay, 1997). In Experiment 1 saccade onset latencies (SOL's) were greater for central versus peripheral presentation for lexical distractors, but not for non-lexical distractors. Experiment 2 showed that repeated presentation of a distractor results in reduced SOL's at central presentation, regardless of lexical status. In Experiment 3 differences in saccade onsets were obtained between two types of lexical distractor when presented at parafoveal locations. Detailed analysis revealed that although SOL's are modulated by distractor complexity, RDE magnitudes are not.